REVISI UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK DALAM DIMENSI POLITIK HUKUM - Irman Syahriar (The Juris, 2021)
Freedom to express thoughts and freedom of opinion as well as the right to obtain information through the use and utilization of Information and communication technology aimed at advancing the general welfare, and educating the nation's life as well as providing a sense of security, justice and legal certainty for users and Electronic System Operators. Law Number 11 of 2008 and undergoing amendments to Law Number 19 of 2016 concerning Electronic Information and Transactions (UU ITE) is the first Law in the field of Information Technology and Electronic Transactions as a much-needed legislation product and has become a pioneer that laying the basis for regulations on the utilization of Information Technology and Electronic Transactions. However, in reality, the implementation journey of the ITE Law has encountered problems. Discourse on the revision of Law (UU) No. 19 of 2016 concerning Information and Electronic Transactions (ITE) sticks out after President Joko Widodo stated that its implementation is often detrimental to the public. Jokowi's statement was made at the opening of the TNI-Polri Leadership Meeting at the State Palace, Jakarta, Monday (15/2/2021). According to Jokowi, recently more and more citizens have reported to the police with reference to the alleged violation of the ITE Law.